SOSIALISASI KEBIJAKAN PEMERINTAH CABUT HET MINYAK GORENG KEMASANDI JAKARTA - Sardjana Orba Manullang (JOURNAL OF COMMUNITY DEDICATION, 2021)
Background: socialization of government policies by revoking the HET for packaged cooking oil so that market players, both producers and consumers, are aware of the policies issued by the government, so that unscrupulous hoarders will be immediately sanctioned and followed up legally. Objective: to stabilize the market share economy and the market mechanism remains stable so that cooking oil does not run out of the country. Method: problem solving with a qualitative descriptive approach by conducting community service research. Result: with this policy from the government, especially entrepreneurs producing cooking oil can breathe a sigh of relief because they follow international and national CPO prices, so for cooking oil raw materials remain at market standards so that prices are in accordance with the purchase of raw materials and entrepreneurs do not suffer losses, so to ensure that price can apply in the market, the government will provide subsidies for retail cooking oil through the Palm Oil Plantation Fund Management Agency.